Pengaruh Kampanye Go-Pay Day Food and Beverage terhadap Perilaku Konsumtif Pengguna (Survei Pada Karyawan P.T Pionir Maxima Mutu Indonesia) - Cyntia Triana Simanjuntak; H.H. Daniel Tamburian (Prologia, 2020)
The title of this research “Campaign Influence Go-Pay Pay Day food and beverage To The User’s Consumptive Behaviour (Surveyed to one of the employees of P.T Pionir Maxima Mutu Indonesia)”. In this research, 100 respondents were participating in filling up the questionnaire by using a google form, where the terms and conditions to be a respondent is using Go-Pay on the Pay Day Food and beverage. The purpose of this research is to discover the impact of the campaign of Go-Pay Pay Day food and beverage towards Consumptive behaviour user.This research identifies the impact of the campaign Go-Pay Pay Day food and beverage towards Consumptive behaviour user and the cause of the user's consumption in using Go-Pay on the Pay Day food and beverage. This research also utilizes correlation methods which are gatherers data to determine if there are relations and the level of relationship between the two variables. The data of the research has been obtained from the questionnaire, literature review, journal, and online data. The theory that has been used in this research was The Theory of Communication, Campaign and Consumptive Behaviour. The result of this showing the campaign of Go-Pay Pay Day food and beverage has a positive impact and significant effect towards the Consumptive Behaviour on the employee of P.T Pionir Maxima Mutu Indonesia. Penelitian ini berjudul “Pengaruh Kampanye Go-Pay Pay Day food and beverage terhadap perilaku Konsumtif Pengguna (Survei Pada Karyawan P.T Pionir Maxima Mutu Indonesia)”. Penelitian ini mengambil sampel 100 responden dengan penyebaran kuesioner menggunakan google form, dimana syarat menjadi responden adalah populasi yang menggunakan Go-Pay pada saat Payday food and beverage. Tujuan penelitian ini adalah untuk mengetahui pengaruh Kampanye Go-Pay Pay Day food and beverage terhadap Perilaku Konsumtif Pengguna. Penelitian ini mengidentifikasi masalah pengaruh kampanye Go-Pay Pay Day food and beverage terhadap perilaku konsumtif pengguna serta Penyebab konsumtifnya pengguna dalam pemakaian Go-Pay pada saat Pay Day food and beverage. Penelitian ini menggunakan metode korelasi yaitu penelitian yang melibatkan tindakan pengumpulan data guna menentukan, apakah ada hubungan dan tingkat hubungan antara dua variabel. Data penelitian diperoleh dari kuesioner, studi pustaka, jurnal, dan data online. Teori yang digunakan dalam penelitian ini adalah Teori Komunikasi, Kampanye dan Perilaku Konsumtif. Hasil penelitian menunjukkan  Kampanye Go-Pay Pay Day food and beverage memiliki pengaruh positif dan signifikan terhadap Perilaku Konsumtif pada Karyawan P.T Pionir Maxima Mutu Indonesia.